Health information and health-seeking behaviour in Yemen: perspectives of health leaders, midwives and mothers in two rural areas of Yemen - Dalia Hyzam; Mingyang Zou; Michael Boah; Abeer Saeed; Chenrui Li; Shixu Pan; Jinhe Zhai; Li-Jie Wu (BMC, 2020)
Abstract Background Humanitarian crises can lead to the rapid change in the health needs of women and newborns, which may give rise to a complex situation that would require various interventions as solutions. This study aimed to examine the health education and promotion patterns, health-seeking behaviour of mothers, and barriers to the use of maternal health services from public health facilities in two rural areas of Yemen. Methods We used a qualitative approach. We conducted in-depth interviews and focus group discussions with frontline health professionals and mothers respectively. Nine in-depth interviews were conducted with the health professionals, including 4 health leaders and 5 midwives, and 2 focus group discussions with mothers aged 18-45 years in Abyan and Lahj. Thematic analysis approach was used to analyze the data in Atlas.ti (version 8) Software. Results Our data showed that health education and promotion activities on maternal health were ad hoc and coverage was poor. Maternal health services were underutilized by women. According to the data from the focus group discussions, the poor quality of services, as indicated by inadequate numbers of female doctors, lack of medical equipment and medicines, and costs of services were barriers to use maternal health services. Moreover, the use of prenatal and postnatal care services was associated with women's' perceived need. However, according to the health professionals, the inadequate human resource, workload, and inadequate funding from government have contributed significantly to the perceived quality of maternal health services provided by public health facilities. Despite the identified barriers, we found that a safe motherhood voucher scheme was instituted in Lahj which facilitated the use of maternal health services by disadvantaged women by removing financial barriers associated with the use of maternal health services. Conclusion This study identified several obstacles, which worked independently or jointly to minimize the delivery and use of health services by rural women. These included, inadequate funding, inadequate human resources, poor quality of health services, and high cost of services. These barriers need to be addressed to improve the use of reproductive health services in Yemen.